Feasibility of colocating dental hygienists into medical practices. (21st March 2013) - Braun, Patricia A.; Kahl, Shelby; Ellison, Misoo C.; Ling, Sarah; Widmer‐Racich, Katina; Daley, Matthew F.
Abstract: Objectives: To test the feasibility of colocating registered dental hygienists (RDHs) into medical practices and to evaluate parent/caregiver oral health characteristics. Methods: From December 2008 to April 2009, we colocated five RDHs into five medical practices identified for their service to low‐income children. Dual‐function exam rooms were built in each office. Caregiver–child dyads were recruited from the practices for program evaluation. We used both qualitative (key informant interviews) and quantitative (survey) methods to evaluate the project. Feasibility was measured by assessment of RDH and practice factors that facilitated and/or created barriers to colocation, sustainability of services 5 years after colocation, and caregiver satisfaction with services. Caregiver oral health knowledge, attitudes, beliefs, and behaviors were also measured. Results: Over 27 months, five part‐time RDHs provided care to 2, 071 children. Children of caregiver–child dyads ( n = 583) recruited for evaluation were young (mean age = 1.8 years), white (46 percent), non‐Hispanic (56 percent), and publicly insured (68 percent Medicaid/11 percent State Children's Health Insurance Plan). Key informant interviews revealed various factors that facilitated and created barriers to program adoption, implementation, and sustainability. Most barriers were overcome. Five RDHs remained in the practices 2 years after program initiation and four remained after 5 years. At 1 year, 27 percent of caregiver–child dyads returned for evaluation and were highly satisfied with services. Caregivers reported favorable oral health characteristics and few barriers to receiving preventive dental care at baseline and 1‐year follow‐up. Conclusions: Colocating RDHs into medical practices is feasible and an innovative model to provide preventive oral health services to disadvantaged children.